Práctica de valores éticos y su incidencia en el rendimiento escolar en los niños y niñas del Segundo Grado de la Unidad Educativa "La Maná", año lectivo 2016-2017 - Pilaguano Pilatasig, Ercilia Janeth (2017)
The project had the participation of the educational community, so helped students to strengthen the ethical values that today are very important to improve the academic progress of the children in educational institutions. The objective was to strengthen the use of the ethical values of the students of the institution, by means of the socialization of the seminar workshop to improve academic progress. Based on the result, we were able to determine that the inappropriate behavior of the students helped the comprehensive education of the students. The purpose was to determine the level the use of valuesand its influence on school performance. We apply the methodology such as: seminary workshop, group work and games, focused on ethical values; so that we contribute with the educational community to the improvement in the behavior and its academic progress in the socio-educational environment. We kept in mind the importance of education in values and its use. Hence this the fundamental basis that allowed to involve the educational community rescuing the ethical values, It reached a great socio-educational impact, considering that this process contributes a tool to organize to the educational community achieving significant goals likewise improving quality standards in education and society, helping 119 children from the La Maná Educational Unit. Getting creative, participatory, disciplined and performing students.